A typological and archaeological study of human and animal representations in the plastic art of Palestine during the Iron Age - Holland, T (1975)
﻿ Palestine has one of the longest histories of archaeological exploration in the Near East "because the recovery of its material remains has "been of great value in interpreting biblical literature, which in turn has shed much light on the ancient history of the Levant in general. In order to establish the chronological setting, Sir Flinders Petrie was the first Near Eastern archaeologist to devise a system of sequence dating based upon the scientific study of pottery in its stratigraphical position within a mound. As a result of his researches in Palestine, the first systematic attempt was made to record a corpus of pottery representing all periods of occupation during which pottery occurred. The result was the publication by Duncan of the Corpus of Palestinian Pottery (London, 1930). Since 1930, the study of pottery types has been greatly refined and enlarged so that at least the general periods of Palestine's history can now be defined in some detail by known pottery types. The best modern compilation of the pottery from its beginnings in the Neolithic period to the end of the Iron Age is Amiran's Ancient Pottery of the Holy Land (Jerusalem, 1969). Many special studies of pottery, the latest being Franken's In Search of the Jericho Potters (Leiden, 1975), employ both old and new methods of typology in ceramic studies in an effort to understand more completely the cultural and chronological changes within the various periods of Palestinian history ... [see pdf file for full abstract].